The Role of Wisdom in the Cross-Cultural Adaptation of Chinese Visiting Scholars to Canada: A Mediation Model - Bao, Dan; Zhou, Liqing; Ferrari, Michel; Feng, Zhe; Cheng, Yahua (Frontiers in Psychology, 2022)
This study examines the role of wisdom in the cross-cultural adaptation of Chinese visiting scholars in Canada, as mediated by different coping styles. Path analysis was used to for hypotheses testing. The findings suggest that (1) wisdom measured by 3D-WS and ASTI, independently had direct correlation with social and psychological adaptation, and positively associated with engaged coping (active coping and proactive-reflective coping); (2) the independent effects of 3D-WS and ASTI on social adaptation, psychological adaptation, and life satisfaction were mediated by proactive-reflective coping. (3) wisdom, when measured by 3D-WS, promoted positive psychological adaptation through decreasing passive coping. This study shows that wisdom is a critical factor affecting cross-cultural adaptation, and the use of proactive-reflective coping is a wise way of handling future life challenges.